Fabrication of Sub‐Micrometer‐Sized MoS2 Thin‐Film Transistor by Phase Mode AFM Lithography. Issue 49 (21st September 2018) - Liu, Lianqing; Shi, Jialin; Li, Meng; Yu, Peng; Yang, Tie; Li, Guangyong
Abstract: The phase mode atomic force microscopy (AFM) lithography and monolayer lift‐off process are combined to fabricate electronics based on 2D materials (2DMs), which remove the need for pre‐fabricating markers and increase the accuracy of the overlay and alignment. The promising phase mode of AFM lithography eliminates the drawbacks of the conventional force mode such as the over‐cut, under‐cut, debris effect, and severe tip wear. The planar size of MoS2 thin‐film transistors is shrunken down to sub‐micrometer by the proposed method, and the fabricated devices demonstrate n‐type characteristics. It offers a more flexible and easier way to fabricate prototypes of sub‐micrometer‐sized 2DMs based devices, and gives the opportunity to explore the size effect on the performance of 2DMs devices. Abstract : A unique mask‐free and marker‐free lithography technique to a fabricate 2D materials (2DMs) thin‐film transistor is developed by utilizing the phase mode of atomic force microscopy, which has down‐sized the device dimension to the nanoscale. It offers a flexible, effective, and low‐cost way to fabricate prototypes of sub‐micrometer‐sized 2DMs based devices, and the opportunities to explore the potential high performance of 2DMs.